2008
DOI: 10.1186/1756-6606-1-11
|View full text |Cite
|
Sign up to set email alerts
|

Impaired long-term memory retention and working memory in sdy mutant mice with a deletion in Dtnbp1, a susceptibility gene for schizophrenia

Abstract: Background: Schizophrenia is a complex genetic disorder caused by multiple genetic and environmental factors. The dystrobrevin-binding protein 1 (DTNBP1: dysbindin-1) gene is a major susceptibility gene for schizophrenia. Genetic variations in DTNBP1 are associated with cognitive functions, general cognitive ability and memory function, and clinical features of patients with schizophrenia including negative symptoms and cognitive decline. Since reduced expression of dysbindin-1 has been observed in postmortem … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

3
84
0

Year Published

2009
2009
2021
2021

Publication Types

Select...
7
1
1

Relationship

1
8

Authors

Journals

citations
Cited by 111 publications
(87 citation statements)
references
References 78 publications
3
84
0
Order By: Relevance
“…[2][3][4] Furthermore, the Sandy mouse, which expresses no dysbindin-1, has been reported to have behavioral abnormalities, cognitive deficits and a synaptic dysfunction that is related to the pathophysiology of schizophrenia. [5][6][7] Identified risk variants of NRG-1 are associated with the reduced white matter volume that is observed in schizophrenic brains. 8 The NRG-1 gene spans 1.2 Mb 9 and gives rise to many structurally and functionally distinct isoforms, through alternative promoter usage.…”
Section: Introductionmentioning
confidence: 99%
“…[2][3][4] Furthermore, the Sandy mouse, which expresses no dysbindin-1, has been reported to have behavioral abnormalities, cognitive deficits and a synaptic dysfunction that is related to the pathophysiology of schizophrenia. [5][6][7] Identified risk variants of NRG-1 are associated with the reduced white matter volume that is observed in schizophrenic brains. 8 The NRG-1 gene spans 1.2 Mb 9 and gives rise to many structurally and functionally distinct isoforms, through alternative promoter usage.…”
Section: Introductionmentioning
confidence: 99%
“…305 Recently, there has been a proliferation of animal model studies that have examined Dtnbp1 in the sandy mouse, which does not express the Dtnbp1 gene. 306 Studies have shown that Dtnbp1 knockout mice display reduced social inter action, impairments in long-term memory retention, spatial memory and working memory, as well as hyperactivity. [306][307][308][309] These mice also have a reduction in the steady state levels of synapsin in the hippocampal formation, a reduction in DA, but normal glutamate levels.…”
Section: Dystrobrevin Binding Protein I (Dtnbp1)mentioning
confidence: 99%
“…306 Studies have shown that Dtnbp1 knockout mice display reduced social inter action, impairments in long-term memory retention, spatial memory and working memory, as well as hyperactivity. [306][307][308][309] These mice also have a reduction in the steady state levels of synapsin in the hippocampal formation, a reduction in DA, but normal glutamate levels. 308,309 Given the findings from both animal model and human association studies, it would appear that DTNBP1 is an influential gene in the development of schizophrenia-related biomarkers and schizophrenia, respectively.…”
Section: Dystrobrevin Binding Protein I (Dtnbp1)mentioning
confidence: 99%
“…Some studies indicate that these mice have increased T-maze performance while other find the converse Takao et al, 2008;Karlsgodt et al, 2011;Papaleo et al, 2012). Alternatively, dysbindin knockout mice display impaired spatial reference memory and novel object recognition performance (Karlsgodt et al, 2011;Papaleo et al, 2012).…”
Section: Relating Behavior To Eeg/lfp Validation Of Modelsmentioning
confidence: 99%